Hepatitis E Virus Genotype 1 Cases Imported to Portugal from India, 2016 - Mesquita, JR (2018)
Hepatitis E in industrialized countries is mainly associated with genotype 3 hepatitis E virus (HEV) and normally causes a sporadic self-limiting disease in immunocompetent individuals. Unlike genotype 3, genotypes 1 and 2 circulate in developing countries, produce severe disease and occur in the epidemic form. Hepatitis E occurring in travellers returning from endemic areas in developing countries is not a novel epidemiological occurrence, however the vast majority of cases remain to be genetically studied. The present study describes two cases of severe acute hepatitis E that required hospitalization for 6 and 9 days in two individuals of Indian nationality that had recently migrated to Portugal to work. The retrieved HEV sequences both belonged to genotype 1 and had a high degree of nucleotide sequence identity, clustering with strains isolated in India and Nepal, in 2013 and 2014. Confirmed HEV genotypes of increased pathogenicity like genotype 1 are being introduced into otherwise naïve populations of industrialized countries such as European countries with consequences difficult to predict. As far as we know the present study is the first in Portugal to describe and genetically characterize imported cases of hepatitis E infection caused by HEV genotype 1.